PENINGKATAN KETERAMPILAN BERBICARA SISWA MELALUI MODEL PEMBELAJARAN PICTURE AND PICTURE DI KELAS 5 SD NEGERI MANGUNSARI 03 SALATIGA - Febry Damai Riyanti (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2017)
ABSTRACTThis study aims to determine the improvement of students' speaking skills by using the picture and picture model in grade V SD Negeri Mangunsari 03 Salatiga. This type of research is Classroom Action Research. Data analysis technique used is descriptive qualitative data analysis supported by quantitative data. The results of data analysis showed an increase after after the action. This is apparent in the result of comparison between the average score on prasiklus of 19.97, the average score in cycle I increased by 3.36 to 23.33. The average score in cycle II increased by 2.84 to 26.17. The overall increase from prasiklus to cycle II is 6.2.Keywords: Model Picture And Picture, Speech Skills